Personas Jurídicas : Aviso de la Forma - Gobierno Corporativo y Responsabilidad - Derechos y Obligaciones de los Miembros - Divisiones - Fusiones - Conflictos de Interés - Control (Ediciones UC, 2003)
This publication fills the void left in Chile by studies on the subject, only reduced to an analysis of corporations and foundations. The book is structured from the basic considerations on the notion of person and the substratum of legal personality. It analyzes in depth issues such as the nationality of these entities, the abuse of form, their classification, the rights and obligations of their members, their assets, divisions and mergers, conflicts of interest and their control. The work also presents a thoughtful and systematic legal analysis of economic issues and the effective disputes of values and precepts that arise due to the human organization called "legal persons", to examine this part of our reality with the prism of Law. social and economic.